2008
DOI: 10.1128/aem.00694-07
|View full text |Cite
|
Sign up to set email alerts
|

Epiphyton as a Niche for Ammonia-Oxidizing Bacteria: Detailed Comparison with Benthic and Pelagic Compartments in Shallow Freshwater Lakes

Abstract: Next to the benthic and pelagic compartments, the epiphyton of submerged macrophytes may offer an additional niche for ammonia-oxidizing bacteria in shallow freshwater lakes. In this study, we explored the potential activities and community compositions of ammonia-oxidizing bacteria of the epiphytic, benthic, and pelagic compartments of seven shallow freshwater lakes which differed in their trophic status, distribution of submerged macrophytes, and restoration history. PCR-denaturing gradient gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
4
11
0
Order By: Relevance
“…In a recent, qualitative study of the bacterial ammoniaoxidizing community composition that had been conducted in the same system of interconnected shallow freshwater lakes used for the present study, we demonstrated the presence of ␤-AOB on the leaves of submersed macrophytes by means of the PCR-DGGE technique based on the 16S rRNA gene. We showed that the epiphytic, benthic, and pelagic communities significantly differed from each other (12). Those data were confirmed by the findings of the present study and were completed with quantitative data on the numbers of 16S rRNA gene copies of ␤-AOB cells in the three compartments obtained by qPCR and with direct microscopic images.…”
Section: Vol 76 2010supporting
confidence: 77%
See 4 more Smart Citations
“…In a recent, qualitative study of the bacterial ammoniaoxidizing community composition that had been conducted in the same system of interconnected shallow freshwater lakes used for the present study, we demonstrated the presence of ␤-AOB on the leaves of submersed macrophytes by means of the PCR-DGGE technique based on the 16S rRNA gene. We showed that the epiphytic, benthic, and pelagic communities significantly differed from each other (12). Those data were confirmed by the findings of the present study and were completed with quantitative data on the numbers of 16S rRNA gene copies of ␤-AOB cells in the three compartments obtained by qPCR and with direct microscopic images.…”
Section: Vol 76 2010supporting
confidence: 77%
“…The compositions of the ammonia-oxidizing bacterial communities in the benthic, pelagic, and epiphytic compartments were assessed by a nested PCR-denaturing gradient gel electrophoresis (PCR-DGGE) approach involving two primer sets specific for the amplification of DNA from ammoniaoxidizing Betaproteobacteria. The method has been described in detail by Coci et al (12).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations